Homozygous Mutation in the Insulin Receptor Gene Associated with Mild Type A Insulin Resistance Syndrome: A Case Report - DELİL, KENAN (GALENOS YAYINCILIK, 2021)
Insulin receptor (INSR) mutations lead to heterogeneous disorders that may be as severe as Donohue syndrome or as mild as type A insulin resistance syndrome. Patients with severe disorders usually harbor homozygous or compound heterozygous mutations. In contrast, type A insulin resistance syndrome has been associated with heterozygous mutations; homozygous mutations are rarely responsible for this condition. We report a novel, homozygous mutation, p.Leu260Arg in exon 3, of the INSR gene in a female adolescent patient with type A insulin resistance syndrome together with clinical details of her medical follow-up. Different mutations in the INSR gene cause different phenotype and vary depending on the inheritance pattern. This report adds to the literature, increases understanding of the disease mechanism and aids in genetic counseling.
Keywords: Hirsutism; insulin resistance; insulin receptor gene; FAMILY